Identification of Factors Influencing the Seismic Vulnerability Assessment of Non-Engineered Buildings - Catur Singgih; Setya Winarno; Sri Kusumadewi; Albani Musyafa (G-Tech: Jurnal Teknologi Terapan, 2026)
Non-engineered buildings are still prevalent in many developing countries and consistently with the highest levels of associated with earthquakes damage and fatalities. Nevertheless, there are still few comprehensive vulnerability assessment frameworks that concurrently take consideration technical, socio-economic, and environmental factors. The aim of this study is to identify and prioritize the main contributing factors of seismic vulnerability in non-engineered buildings using a systematic, expert-based evaluation technique. A total of 30 decision-makers participated in a questionnaire survey, ranking the importance of 16 factors across the technical, socio-economic, and environmental using a consensus-based method that includes mean aggregation, normalization to determining weights, and ratio test 0.1 threshold to identify significant factors. The technical has the highest weight (0.407), followed by the socio-economic (0.372) and environmental (0.222) domains. At the factors level, building structural condition (T2) had the greatest significance, followed by construction techniques (T5), material quality (T1), environmental conditions and site location (E1), and socio-economic status (SE2). The generated framework and factor weights provide an objective basis to establish vulnerability assessment and can be extended into fuzzy models to support mitigation and retrofitting strategies.